(untitled) (Clinics, 2023)
OBJECTIVES: As patients recovering from the novel coronavirus disease 2019 (COVID-19) present with physical, respiratory, cognitive, nutritional, and swallowing-related impairments and mental health complications, their rehabilitation needs are complex. This study aimed to describe the demographic, clinical, and functional status after the discharge of COVID-19 survivors who underwent intensive multidisciplinary inpatient rehabilitation at the Physical and Rehabilitation Medicine Institute of the University of Sao Paulo Medical School General Hospital and Lucy Montoro Rehabilitation Institute. We determined the most important factors related to the length of inpatient rehabilitation treatment and present the functional outcomes. METHODS: This was a retrospective study based on electronic medical records. In addition to the severity of COVID-19 and length of hospital stay for the management of COVID-19 and comorbidities, we collected sociodemographic data including age, sex, height, and weight. Functional assessments were performed using the Functional Independence Measure (FIM); Short Physical Performance Battery; Montreal Cognitive Assessment; Depression, Anxiety and Stress Scale; Revised Impact of Events Scale; bioelectrical impedance; Functional Oral Intake Scale; oropharyngeal dysphagia classification; and nutritional assessment. RESULTS: There was a significant improvement in FIM before and after inpatient rehabilitation treatment (p<0.0001). Muscle strength and walking capacity were significantly improved (p<0.01). The most important factors related to the length of inpatient rehabilitation treatment were improvement in FIM scores (Spearman's r=0.71) and gain in lean mass (Spearman's r=0.79). CONCLUSIONS: Rehabilitation of patients after COVID-19 recovery improves their functional status and should be considered in the post-acute phase for selected patients with COVID-19.